THE EFFECTIVENESS OF MINDFULNESS-BASED COGNITIVE THERAPY IN REDUCING ANXIETY AMONG MEDICAL STUDENTS - Rofi, Muhammad; Poppy Dewi Ratih; Octarini Prasetyowati (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Anxiety is a common psychological disorder among medical students, marked by chronic apprehension and physiological manifestations including muscle tension, perspiration, and shortness of breath. These symptoms may hinder cognitive performance, academic achievement, and overall psychological resilience, potentially affecting the future proficiency of medical professionals. This study aimed to evaluate the efficacy of Mindfulness-Based Cognitive Therapy (MBCT) in reducing anxiety symptoms among medical students. An experimental research design was used, utilizing a one-group pretest-posttest approach, involving eight participants who met the established inclusion criteria. The intervention consists of eight weekly MBCT sessions, each lasting 90 to 120 minutes. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. HARS scores indicated a statistically significant reduction in anxiety level following the MBCT intervention (Z = –2.111ᵇ, p = 0.035). These findings suggest that MBCT serves as an effective therapeutic approach for reducing anxiety among medical students in higher education settings.